Lean Hospitals as a concept supporting the sustainable development of hospitals - Korkosz-Gębska, Jolanta (Lean hospitals jako koncepcja wspomagająca zrównoważony rozwój szpitali, 2019)
Hospital management is an interdisciplinary issue, combining economic, technical, legal and IT aspects. The situation requires the application of complex management methods, which also include the concept of Lean Management (LM). The Lean Management concept applied in healthcare facilities is known as Lean Healthcare (LH) whereas in hospitals – Lean Hospitals. The aim of the article is to present the possibilities of using selected LM tools in improving the functioning of hospitals in the context of their sustainable development. The article focuses mainly on describing the advantages resulting from the application of the 5S method in hospitals, which contributes to saving hospital resources and to eliminating waste. This work is based mainly on secondary sources of information. The applied research methods such as Desk Research and non-participant observation confirmed the validity of using LM to improve the functioning of hospitals
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 9, s. 152-160
Keywords: lean healthcare; lean hospital; 5S; waste; sustainable development; marnotrawstwo; zrównoważony rozwój